1992
DOI: 10.1007/bf00226583
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal growth, ?13C in leaves and stem, and phloem structure of birch (Betula pendula) under low ozone concentrations

Abstract: The growth of potted birch cuttings (one clone of Betula pendula) was studied under low 03 concentrations (0, 0.050, 0.075, 0.100 ~tl 1-1) throughout an entire growing season. With increasing 03 dose, 20-50% of all leaves formed were prematurely shed, while 40-70% of the remaining foliage displayed advanced discoloration by the end of the season. Ozonation affected the S, P and N concentration of leaves and increased ~13C in leaves and stem, while the CO2 assimilation rate declined with increasing CO2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 23 publications
12
74
0
Order By: Relevance
“…Reduced root growth at elevated O $ may be caused by reductions in available C from photosynthesis (Saxe, 1991) ; an increased C demand for aboveground repair or replacement mechanisms (Kelly et al, 1993 ;Pearson & Mansfield, 1994) ; and\or by impaired phloem functioning (Spence et al, 1990 ;Matyssek et al, 1992). In our study, at least part of the declining root : shoot ratio in the 12 provenances could have been caused by a decline in photosynthesis, though the decline of A max became significant only late in the second season.…”
Section: mentioning
confidence: 54%
“…Reduced root growth at elevated O $ may be caused by reductions in available C from photosynthesis (Saxe, 1991) ; an increased C demand for aboveground repair or replacement mechanisms (Kelly et al, 1993 ;Pearson & Mansfield, 1994) ; and\or by impaired phloem functioning (Spence et al, 1990 ;Matyssek et al, 1992). In our study, at least part of the declining root : shoot ratio in the 12 provenances could have been caused by a decline in photosynthesis, though the decline of A max became significant only late in the second season.…”
Section: mentioning
confidence: 54%
“…Wang ef a/., 1986;Pye, 1988 ;Mortensen & Skre, 1990;. Matyssek et al (1992) have previously reported advanced discoloration of birch leaves with increasing ozone concentration by the end of the growing season in field fumigation chambers. Our observations also indicate a clear connection between elevated ozone concentrations and enhanced seasonal yellowing of leaves in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among broadleaved trees it appears that the growth of birch, aspen and poplar is particularly sensitive to O $ . Commonly, growth reductions or premature senescence are reported within one exposure season (birch, Matyssek et al (1992, Pa$ a$ kko$ nen, Holopainen & Ka$ renlampi (1995 a, 1997 a), Pa$ a$ kko$ nen et al (1995 b, 1996) ; American aspen (Populus tremuloides), Keller (1988) ; hybrid poplar (Populus euramericana), Matyssek et al (1993), Mooi (1980)). European beech is also O $ -sensitive, and growth reductions and premature senescence have been detected in several recent studies (Ku$ ppers et al, 1994 ;Pearson & Mansfield, 1994 ;Braun & Flu$ ckiger, 1995 ;Krause & Ho$ ckel, 1995 ;Steingro$ ver et al, 1995 ;Mikkelsen & Jorgensen, 1996 ;Mortensen, Bastrup-Birk & Ro-Poulsen, 1996).…”
Section: Seedlings\saplingsmentioning
confidence: 99%